Bola na rede e o povo nas ruas! Estado Novo, imprensa esportiva e torcedores na Copa do Mundo de 1938 - Machado, Felipe Morelli (2011)
This thesis aims at analyzing the Brazilian participation in the Football World Cup disputed in June 1938, in France, an achievement that took on different meanings for the New State, the sports press and the supporters. It is about an emblematic moment for perceiving football as a social and symbolic place of conservation and, at the same time, of posing questions about the order in force, within a dictatorial context. From the dealing with the huge sports newspaper, in the capital cities of São Paulo and Rio de Janeiro (Brazil), it was observed the repercussion of that sports episode, from north to south, spilling over into the national life. In this happening, football arises not only as an element capable of congregating, among the same supporters, individuals from the most varied social cultural profiles, but also as a quarreling space, with disagreements and rivalries, which are found in the construction base of the national feeling